1990
DOI: 10.2307/1591383
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of H13 Nephropathogenic Infectious Bronchitis Virus

Abstract: A nephropathogenic Massachusetts strain of infectious bronchitis virus (IBV) designated H13-IBV was isolated from the kidneys of commercial broilers. H13-IBV caused respiratory distress, depression, and diarrhea in specific-pathogen-free chickens. Gross renal lesions included pale coloration, swelling, and urate deposition. Histologic renal changes were interstitial mononuclear cell infiltration and degeneration and necrosis of tubular epithelial cells. Lesions in respiratory tissues included thickening and ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
4
15
1
2
Order By: Relevance
“…However, unlike previous studies where either severe kidney damage (Butcher et al, 1990;Chen et al, 1996) or alterations to the reproductive tract (Crinion & Hofstad, 1971) was reported following M41 infection, in our study no remarkable lesions or presence of viral RNA was detected in the other organs. This discrepancy might be caused by different passage levels, experimental conditions and design, breed or age of the birds, or by the use of different strains of M41.…”
Section: Discussioncontrasting
confidence: 99%
“…However, unlike previous studies where either severe kidney damage (Butcher et al, 1990;Chen et al, 1996) or alterations to the reproductive tract (Crinion & Hofstad, 1971) was reported following M41 infection, in our study no remarkable lesions or presence of viral RNA was detected in the other organs. This discrepancy might be caused by different passage levels, experimental conditions and design, breed or age of the birds, or by the use of different strains of M41.…”
Section: Discussioncontrasting
confidence: 99%
“…If air sac involvement occurs, there is edema, epithelial cell desquamation, and some fibrinous exudates within 24 hrs (Riddell, 1987). Janse et al, (1994) also reported the comparable findings like deciliation, sqamous metaplasia, cellular infiltration, edema of mucous and exudates as noticed by other workers (Butcher et al, 1990;Mahdavi et al, 2007). The virus replicates in ciliated epithelial cells causing deciliation, odema, desquamation, hyperplasia and mononuclear cell infiltration.…”
Section: Resultssupporting
confidence: 78%
“…were recorded in the flocks. Butcher et al, (1990), Kinde (1991) and Mahgoub et al, (2010) also with recorded similar clinical findings. The mortality ranged from 5.4 to 35.2% with average mortality of 12.2% were recorded (Table 1).…”
Section: Resultssupporting
confidence: 61%
“…The histological changes of the trachea epithelium were deciliation, squamous metaplasia, cell infiltration, oedema of the mucosa and exúdate. These results are similar to those described by Butcher et al (1990), Purcell & McFerran (1972) and Hofstad (1945).…”
Section: Trachea and Lungssupporting
confidence: 92%